Efektivitas Pelayanan Pembayaran Pajak Kendaraan Bermotor melalui Aplikasi E-Samsat pada Unit Pelayanan Pendapatan Daerah Samsat Banjarmasin 1 - Gusti Kintan Wardhani; Rika Novyanti; Rohayati Rohayati; Rini Amelia (P3M Politeknik Negeri Banjarmasin, 2022)
The purposes of this study are (1) to determine the effectiveness of motor vehicle tax payment services through the E-Samsat application at the Regional Revenue Service Unit Office of Samsat Banjarmasin 1, and (2) to determine the comparison between users of conventional motor vehicle tax payment services and those using the application. E-Samsat at the Regional Revenue Service Unit Office of Samsat Banjarmasin 1. The research method used in this research is descriptive research. The population in this study is the public in the service of paying motorized vehicle taxes at the Regional Revenue Service Unit Office of Samsat Banjarmasin 1. The sample in this study was 124 respondents. Sources of data in this study are primary data and secondary data. The results showed that (1) the effectiveness related to procedures and services, E-Samsat can facilitate people who are far from the city in order to minimize delays, because it can be done anytime and anywhere, and (2) this e-samsat application, customers feel the ease of the application. Therefore, it is recommended that services through E-Samsat can be further maximized so that the community is satisfied in using the E-Samsat services, such as the certainty of the schedule and duration of services resulting from effective e-Samsat services and clarity of service procedures.